Exposição à realidade virtual como forma de diminuir a ansiedade de falar em público - Ortega, Carolina Machado (2019)
This study aimed to develop and test a virtual environment called PsicoAVR as a way to reduce the anxiety of public speaking. Nine participants were divided in three groups: (1) Virtual Reality Group (GRV); (2) Behavioral Therapy Group (GTC); and (3) Waiting List Group (GLE). Participants of the first group were submitted to the virtual environment, in which they were gradually exposed to situations that contained phobic stimuli. The second group participated in behavioral therapy sessions with exposures to phobic stimuli within the psychologist’s office, without the use of virtual reality. The third group only answered to the same anxiety questionnaires applied in the other two groups. The electrical conductance of the skin was evaluated. GRV and GTC participants self-evaluated their social performance as well as were evaluated by observers. The reports from participants of the two intervention groups (GRV and GTC) indicated they were able to expose themselves to natural situations that previously elicited anxiety response. Data on skin conductance indicated that participants in both intervention groups decreased anxiety during the sessions. GRV participants presented a greater generalization to their natural environment, gradually exposing themselves, and were less anxious in the generalization sessions than GTC participants. The evaluation of social performance showed that the majority of the participants self-evaluated in a derogatory manner. All participants, in both intervention groups, improved speech performance and frequency of gaze and decreased anxiety. In the follow-up, which occurred one month after the intervention, the GRV and GTC participants maintained their results. GLE participants did not change their baseline data. The study concluded that virtual reality facilitated the generalization of appropriate behaviors to the natural environment and reduced the anxiety of public speaking